2021
DOI: 10.1007/s00508-021-01824-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdown during the COVID-19 pandemic on number of patients and patterns of injuries at a level I trauma center

Abstract: Summary Objective The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) and its associated illness, coronavirus disease 2019 (COVID-19), has led to a global health crisis burdening frontline emergency departments, including orthopedic and trauma units. The aim of this study was to provide an overview of the impact of the lockdown secondary to the pandemic on patient numbers and pattern of injuries at the department of traumatology of the Medical University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 22 publications
2
38
1
8
Order By: Relevance
“…Nine studies reported the impact of lockdown during the Covid-19 pandemic on injuries at level I trauma centres in Europe [ 40 48 ]. Compared to the pre-Covid-19 era, there was a significant reduction between 12.2% and 69.75% of patients presenting to trauma departments [ 40 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies reported the impact of lockdown during the Covid-19 pandemic on injuries at level I trauma centres in Europe [ 40 48 ]. Compared to the pre-Covid-19 era, there was a significant reduction between 12.2% and 69.75% of patients presenting to trauma departments [ 40 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported the impact of lockdown during the Covid-19 pandemic on injuries at level I trauma centres in Europe [ 40 48 ]. Compared to the pre-Covid-19 era, there was a significant reduction between 12.2% and 69.75% of patients presenting to trauma departments [ 40 48 ]. Three studies showed no significant reductions of major trauma, defined as an injury severity score (ISS) of greater than 15 [ 42 , 44 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nia et al [ 11 ] described a decrease in all patient admissions by almost 70% in 2020. Compared with other conditions, the incidence of hip fractures was less affected by the social lockdown in the COVID period.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Italy that investigated wrist and hand injuries found a significant reduction in traffic crashes during the lockdown period than in 2019 (10). Similarly, a decrease in trauma has been observed during the COVID-19 pandemic in Netherlands, New Zealand, Australia, South Africa, and Austria (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 90%